Pengembangan Kartu Praktis Tashrifan Pada Mata Pelajaran Shorof Bab Wazan: Studi Kasus Kelas III Mi Al-Anwar Cangkringrandu Perak - Nisa', Kharisatun (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Abstract: Shorof (Morphology) is an important branch of knowledge for students to learn, as it serves as the foundation of all other disciplines. Shorof plays a crucial role in forming every sentence. By studying shorof, we can also better understand and analyze the meanings contained in the Qur'an and Hadith.However, the learning of shorof is often monotonous, as the teacher explains the material while students merely listen. Therefore, the researcher introduced the practical tashrifan card teaching material, which is developed from a traditional shorof textbook focusing on the wazan (patterns) topic, specifically for third-grade students at the Madrasah Ibtidaiyah (Islamic elementary school).This research is a type of R&D (Research and Development) study. The data collection instruments used included interviews, observations, and questionnaires.The results of the study show that: 1. The practical tashrifan card teaching material is implemented using lecture and practice methods. 2 Its development follows the Borg and Gall model with several development procedures. 4. Students were very enthusiastic and found it easier to understand shorof lessons due to the brief explanations, numerous exercises, and various engaging images. 5. The improvement in learning motivation is evident from the assessment instrument results, showing an average score of 66% before using the practical tashrifan card material, and 84% after its implementation, indicating an increase in students' learning motivation.